MiR-331-3p Links to Drug Resistance of Pancreatic Cancer Cells by Activating WNT/β-Catenin Signal via ST7L. (11th September 2020) - Zhan, Ting; Chen, Xiaoli; Tian, Xia; Han, Zheng; Liu, Meng; Zou, Yanli; Huang, Shasha; Chen, Aifang; Cheng, Xueting; Deng, Junsheng; Tan, Jie; Huang, Xiaodong
Background: Pancreatic cancer is an aggressive type of cancer with poor prognosis, short survival rate, and high mortality. Drug resistance is a major cause of treatment failure in the disease. MiR-331-3p has been reported to play an important role in several cancers. We previously showed that miR-331-3p is upregulated in pancreatic cancer and promotes pancreatic cancer cell proliferation and epithelial-to-mesenchymal transition–mediated metastasis by targeting ST7L. However, it is uncertain whether miR-331-3p is involved in drug resistance. Methods: We investigated the relationship between miR-331-3p and pancreatic cancer drug resistance. As part of this, microRNA mimics or inhibitors were transfected into pancreatic cancer cells. Quantitative polymerase chain reaction was used to detect miR-331-3p expression, and flow cytometry was used to detect cell apoptosis. The Cell Counting Kit-8 assay was used to measure the IC50 values of gemcitabine in pancreatic cancer cells. The expression of multidrug resistance protein 1, multidrug resistance-related protein 1, breast cancer resistance protein, β-Catenin, c-Myc, Cyclin D1, Bcl-2, and Caspase-3 was evaluated by Western blotting. Results: We confirmed that miR-331-3p is upregulated in gemcitabine-treated pancreatic cancer cells and plasma from chemotherapy patients. We also confirmed that miR-331-3p inhibition decreased drug resistance by regulating cell apoptosis and multidrug resistance protein 1, multidrug resistance-related protein 1, and breast cancer resistance protein expression in pancreatic cancer cells, whereas miR-331-3p overexpression had the opposite effect. We further demonstrated that miR-331-3p effects in drug resistance were partially reversed by ST7L overexpression. In addition, overexpression of miR-331-3p activated Wnt/β-catenin signaling in pancreatic cancer cells, and ST7L overexpression restored activation of Wnt/β-catenin signaling. Conclusions: Taken together, our data demonstrate that miR-331-3p contributes to drug resistance by activating Wnt/β-catenin signaling via ST7L in pancreatic cancer cells. These data provide a theoretical basis for new targeted therapies in the future.